The Role of Universities in Increasing Social and Economic Resilience through the Community Empowerment Program in Cirebon City - Sitti Faoziyah (International Journal of Science and Society, 2022)
The purpose of this study was to analyze the role of universities in increasing social resilience and economic resilience through community empowerment. To achieve this goal, the research design used is structural equational modeling (SEM) by investigating the direct influence between community empowerment carried out by universities on social security, economic resilience, and community welfare both directly and indirectly. The method used is quantitative research with a survey approach. The research population is all poor people of Cirebon City as many as 26 thousand people spread over five sub-districts and 22 urban villages. The sampling technique is proportional random sampling technique. The sample size was obtained by using the formula for the number of indicators 27 multiplied by 5 to obtain a sample size of 185 people. The data was obtained by using a survey method by distributing questionnaires. The data were analyzed using the Smart-PLS 3.0 application. Based on the results of data analysis, it is concluded that there is a direct effect of community empowerment carried out by universities on social security, economic resilience, and community welfare. This study also found that there was a direct influence of social security and economic resilience on the welfare of the community. Furthermore, this study also found the indirect effect of community empowerment on community welfare through social security and through economic resilience.